Konsep Tadris Ekonomi di Dalam Al-Qur’an - Hikmatullah Jamud (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2017)
Since humans are born on earth he will always try to maintain their existence and function as khalifah. To realize all that God has provided resources (resources and facilities) of life that can be accessed by humans in meeting needs such as food and clothing, security and improving the standard of economic life. Therefore humans are required to develop production and distribution processes that are supported by the development of economic systems, communication and information systems. As a provision to maintain human existence, manhaj al-hayat and wasilatul Hayat were given. Manhaj Hayat is all the rules of human life that are sourced from the Qur'an and Assunnah. And We send down to you Al-Kitab (Al-Quran) to explain everything and instructions and grace and good news for those who surrender